Передумови використання електромагнітних сил у технологіях рафінування алюмінієвих сплавів від неметалевих включень - Фікссен, В.М.; Смірнов, О.М.; Горшков, А.О.; Лакомська, Л.М.; Васильев, Д.С. (Physico-technological Institute of Metals and Alloys, 2024)
In the production of aluminum castings, the problem of removing non-metallic inclusions (NMIs) is very relevant. A modern efficient way of refining aluminum alloys is filtration through ceramic foam filters. However, their capabilities for retaining small NMIs are limited, since the dimensions of the smallest cells are much larger than the dimensions of the NMIs to be retained. The retention of such particles occurs due to their coagulation and adhesion inside the filter. To enhance the role of these two processes, additional effects on the melt passing through the filter are required. An analysis of current trends shows that at present the most promising application of electromagnetic factors is to create physical conditions in the filter cells, under which the role of coagulation and adhesion will significantly increase. The article describes the main electromagnetic phenomena, using which the task can be solved and specific ways can be outlined to create a technology for the separation of NMIs in aluminum alloys using electromagnetic factors. The basis of electromagnetic influences is the interaction of electric current with a magnetic field. Electric current can interact with both its own and external magnetic field. In both cases, the Lorentz force arises, which creates a pressure gradient in the liquid metal. The direction of the vector of this gradient can be chosen arbitrarily. In a particular case, it may coincide with the direction of the gravitational gradient or be opposite to it. A force opposite to the direction of the vector of the artificial pressure gradient will act on the NMIs located in the pores of the filter. As a result of this factor, it is possible to control the direction of movement of the NMIs. For example, if the pressure gradient vector is directed away from the pore walls, then the role of NMIs adhesion to the filter material will increase and favorable conditions will be created for their coagulation. As a result, an increase in the probability of retaining NMIs, which are much smaller than the pore sizes of the filter, is expected.